Madness and the Apostle: Paul’s Jewishness in the Euthalian Prologue to the Letters of Paul and in the Writings of John Chrysostom - Drake, luke (Vigiliae Christianae, 2024)
The Euthalian Prologue to the Letters of Paul is found in hundreds of late ancient and medieval editions of the Pauline corpus, presenting readers with a prefatory biography of the apostle that both aligns and departs from canonical traditions. Notably, the Prologue depicts Paul’s violence against early Christian assemblies as a manifestation of Jewish μανία, triggered by prophetic foresight and healed by Christ on the road to Damascus. Previous studies primarily examine the Prologue’s connection to canonical sources. This article explores its relationship with other late ancient expressions of Paul’s life. It argues specifically that the Prologue’s depiction of Paul has been shaped – either directly or indirectly – by the writings of John Chrysostom, based on otherwise unique shared thematic elements. Its findings contribute to our understanding of the Prologue’s nebulous origins, its rhetorical objectives, and Chrysostom’s already massive impact on the reception of Pauline literature and tradition in the late ancient and medieval periods.